COX-2 and TGF- expression in proliferative disorders of canine prostate - Rodrigues, Marcela M.P.; Di Santis, Giovana W.; Moura, Veridiana M.B.D. de; Amorim, Renée L. (Brazilian Journal of Veterinary Pathology, 2010)
COX-2 and TGF- expression was determined in order to correlate non-neoplastic lesions, preneoplastic lesions and carcinoma in the prostate of dogs. The results show that neoplastic and preneoplastic lesions express more COX-2 and TGF- when compared to carcinomas, which suggests these proteins may cooperate in the process of prostate tumorigenesis.